2013
DOI: 10.1002/pmic.201300284
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomics of dehydration response in the rice nucleus: New insights into the molecular basis of genotype‐specific adaptation

Abstract: Dehydration is the most crucial environmental factor that considerably reduces the crop harvest index, and thus has become a concern for global agriculture. To better understand the role of nuclear proteins in water-deficit condition, a nuclear proteome was developed from a dehydration-sensitive rice cultivar IR-64 followed by its comparison with that of a dehydration-tolerant c.v. Rasi. The 2DE protein profiling of c.v. IR-64 coupled with MS/MS analysis led to the identification of 93 dehydration-responsive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 80 publications
(89 reference statements)
0
11
0
Order By: Relevance
“…However the outcome is affected by genotypic divergence, organ and tissues, developmental stages besides different environmental cues. The proteomics studies revealed the influence and efficacy of such approach to distinguish the landraces, populations, varieties and even species (Jaiswal et al, 2013;Subba et al, 2013).…”
Section: Comparative Tuber Proteome Profilingmentioning
confidence: 99%
“…However the outcome is affected by genotypic divergence, organ and tissues, developmental stages besides different environmental cues. The proteomics studies revealed the influence and efficacy of such approach to distinguish the landraces, populations, varieties and even species (Jaiswal et al, 2013;Subba et al, 2013).…”
Section: Comparative Tuber Proteome Profilingmentioning
confidence: 99%
“…Eluted proteins were electrophoresed on 12% SDS-PAGE. Separated protein bands were identified with liquid chromatography-mass spectrometry combined with electrospray ionization as described earlier (Jaiswal et al, 2013).…”
Section: Pull-down and Yeast Two-hybrid Assaysmentioning
confidence: 99%
“…The fat body is the center of nutrients synthesis and metabolism, and can function as a nutrient sensor to coordinate the growth of organism (Colombani et al 2003). Proteomics is an important tool for researchers to extensively investigate proteomic differences by various biologic treatments (Chitteti et al 2008;Coiras et al 2008;de la Tour et al 2013;Jaiswal et al 2013). For example, proteomic analysis of the posterior silk gland with the extremely low fibroin production revealed the molecular mechanism in which the silk production is low ).…”
Section: Introductionmentioning
confidence: 98%